Relationship Between Interview Performance And Job Performance Of Executives - Gopal Katherason, Logarajah (1998)
This study exammes the relationship between the overall score of interview questionaire with the end of three months appraisal and the end of one year appraisal. Two moderating variables, work experience and qualification were also studies. The sample size used were 102 employees. The results shows that work experience and qualification has no moderating effect on the model. However there exist significant correlation between overall score of interview questionaire and end of one year perfonnance appraisal. The correlation between the overall score of interview questionaire and end of three months performance appraisal shows no significant correlation.